Electroacupuncture attenuates ac4C modification of P16 mRNA in the ovarian granulosa cells of a mouse model premature ovarian failure. Issue 1 (February 2023) - Geng, Zixiang; Liu, Peng; Yuan, Long; Zhang, Kaiyong; Lin, Jiajia; Nie, Xiaoli; Jiang, Huiru; Li, Bingrong; Liu, Te; Zhang, Bimeng
Background: Premature ovarian failure (POF) is a type of pathological aging, which seriously interferes with the fertility of affected women. Electroacupuncture (EA) may have a beneficial effect; however, its mechanism of action is unknown. The purpose of this study was to determine the effect of EA on ovarian function in ovarian granulosa cells (OGCs) in a cyclophosphamide (CTX)-induced mouse model of POF. Methods: Mice were divided into three groups: wild type (WT) group, CTX group and CTX + EA group. EA was administered under isoflurane anesthesia at CV4, ST36 and SP6 for 30 min every 2 days, 2–3 times per week for a total of 4 weeks. Effects of EA on ovarian weight and level of estrogen were examined. The mRNA and protein expression levels of cell cycle–associated proteins were detected and mRNA modifications were analyzed. Results: EA significantly increased ovarian weight and reduced the proportion of atretic follicles in mice with CTX-induced POF (p < 0.05). EA increased the level of estrogen in the peripheral blood of mice and inhibited the modification of total mRNA N4-acetylcytidine (ac4C). A significant increase in the expression of P16 and N-acetyltransferase 10 (NAT10) and a significant decrease in the expression of Cyclin D (CCND1) and cyclin-dependent kinase 6 (CDK6) were observed in the OGCs of POF mice (p<0.05). After EA, P16 and NAT10 expression was decreased, and CCND1 and CDK6 expression was increased. Finally, EA reduced the ac4C modification of P16 mRNA-specific sites in the OGCs of POF mice. Conclusion: This study demonstrated that EA promoted the repair of the ovarian microenvironment by inhibiting the ac4C modification of P16 mRNA to decrease its stability and expression intensity, and by altering the activity of the P16/CDK6/CCND1 axis in OGCs.